A Verbeekina assemblage (Permian fusulinid) from the Baoshan Block in western Yunnan, China. (27th April 2015) - Huang, Hao; Jin, Xiaochi; Shi, Yukun
Abstract A newly discovered Verbeekina assemblage from the Xiaoxinzhai Section in the Baoshan Block in western Yunnan, China, provides additional data for better understanding fusulinid biostratigraphy and the thermal condition of middle Permian (Guadalupian) seawater of this block. This assemblage comprises 11 species of six genera, including Verbeekina, Pseudodoliolina, Sumatrina, Yangchienia, Xiaoxinzhaiella, and ?Rugosochusenella. The age of this assemblage is considered to be Midian (approximately Capitanian), based on combined evidence of stratigraphic position and specific composition. Furthermore, this assemblage bears two unusual attributes: overwhelming dominance of Verbeekina and relatively low total diversity, compared with coeval fusulinids from South China, which represents a paleo-tropical setting during the middle Permian. These features indicate that the Baoshan Block was probably located in a subtropical setting with warm water during the Midian time; however, its water temperature was still not as optimal as the tropical area (e.g., South China) for the diversification of fusulinids.